Acarbose promotes remission of both early and late dumping syndromes in post-bariatric patients - Cadegiani FA (Dove Medical Press, 2016)
Flavio A Cadegiani,1 Osvalmir Sá Silva2 1Division of Endocrinology and Metabolism, Department of Medicine, Escola Paulista de Medicina, Universidade Federal de São Paulo, São Paulo, SP, 2Corpometria Institute, an Obesity and Endocrinology Center, Brasilia, DF, Brazil Objective: Acarbose is a glucosidase inhibitor that slows carbohydrate digestion. It could thus be effective to promote remission of dumping syndrome (DS). Previous studies associating acarbose and late dumping, although not early dumping, have been reported. Herein, we aimed to evaluate the role of acarbose in dumping syndrome prevention and treatment and in resistive exercises resistance in bariatric subjects. Methods: Bariatric patients with DS and complete adherence to diet plan and resistive exercises were included (n=25). Number of early and late episodes, self-referred intensity of each episode, and ability to increase intensity of resistive exercise were evaluated, on a 0–10 scale. Acarbose was administered orally (50 mg) for 6 months, 4–5 times a day before meals. Results: Acarbose administration was associated with a decrease in the number of early (2.18–0.31) and late (2.79–0.12) episodes per week and intensity of each episode (6.10–1.65) and an increase in the ability to perform resistive exercises (3.03–7.12). Complete remission of DS was seen in 21 patients (84%), which persisted for 6 months with the use of acarbose. Conclusion: Acarbose prevented dumping in almost all studied subjects and helped improve exercise capacity. Keywords: dumping syndrome, bariatric surgery, post-bariatric, obesity